Study of Capital and Operation Costs for Reverse Osmosis Desalination Plants - Mohamed, Habiba Mahdy (AUC Knowledge Fountain, 2025)
Desalination is a progressively common solution to supply freshwater in numerous parts of the globe where this resource falls short. Among all desalination techniques, seawater reverse osmosis (SWRO) is the most globally prevalent technology. Evaluating a desalination technology's cost-effectiveness is essential to ensure a well-designed plant can be implemented successfully and within an acceptable budget. In the Egyptian context, where water scarcity heightens the urgency of effective resource allocation, economic indicators such as capital expenditure (CAPEX) and operational expenditure (OPEX) are pivotal in shaping policy and planning decisions. Adopting this integrated financial perspective ensures that desalination projects are not only economically viable within budgetary limits but also sustainable in terms of long-term operational efficiency. Egypt aims to launch several desalination projects with a total planned capacity of 8.85 million m³/day by 2050, with 3.35 million m³/day targeted by 2025 as the first phase of this program. Furthermore, to address the water scarcity, Egypt plans to draw in strategic investors to develop, construct, and operate desalination plants. Cost overruns are a common challenge encountered during the implementation and operation phases of desalination projects in Egypt. This research aims to develop a capital expenditure (CAPEX) estimation tool to support the feasibility study stages of seawater reverse osmosis (SWRO) desalination projects, while also analyzing CAPEX and operational expenditure (OPEX) data from existing plants to provide data-driven insights for investors and planners. The methodology involves identifying key cost components in desalination plants and determining the five most influential cost drivers: membranes, energy recovery devices (ERDs), civil works, intake systems, and pumps. For components such as membranes, pumps, and ERDs, cost estimation models were developed using deterministic equations and correlations with plant-scale parameters including membrane count, pressure vessel configuration, number of trains, and ERD flow rates. In contrast, site-specific elements like civil works and intake systems were handled using user inputs and simple regression models based on available cost data. A detailed cost analysis was conducted on selected SWRO plants for which reliable data was accessible, accompanied by sensitivity analyses to assess the impact of critical variables on total costs. A set of charts was produced to visualize cost trends, highlight key cost components, and compare plant-level variations. The resulting estimation tool offers a simplified and rapid approach for CAPEX forecasting in early project planning and contributes to more informed decision making in Egypt’s ongoing desalination expansion.